Reactor Modeling and Simulation for Intensifying The Propylene Production In A Petrochemical Plant - Chin, S. Y.; Anwaruddin, Hisyam; Norulshahida, Che Din; Haniif, Prasetiawan; Abdullah, Azahari; Ikmal Hisham, Maharon (2013)
In a business environment where the future feedstock is gradually decreasing, a petrochemical plant needs to look into innovative ways of increasing their yields with minimal increase in the feed volume and capital investment. To date, most of the propane dehydrogenation plants have been operating the reactor as a black box and optimization was performed based on feedback from licensor as well as trial and error. Therefore, knowledge in reactor and kinetic modeling is needed to introduce a new level of understanding to the catalytic step in the plant for the optimization purposes. In the present work, the dehydrogenation of propane to propylene in adiabatic radial-flow moving bed reactor was studied. Several meetings and industrial lecture sessions were conductedto exchange information required for the reactor modeling and simulation. Rate expressions developed from lab scale reactor were considered for the main reaction, side reactions and deactivation kinetics, incorporating the reversibility of dehydrogenation reaction. The model was solved numerically by dividing the reactor into differential isothermal moving-bed reactors. The kinetic parameters were fine-tuned and the reactor model was validated using the plant data obtained at different operating parameters. The conversion of propane to propylene was found to be equilibrium limited in commercial-sized reactors. The model predicted the trends of the reactor performance in terms of conversion, yield, temperature, and catalyst activity. The graphical user interface was developed to simplify the future usage of the model by the plant personnel. The accuracy of the developed model requires further refinement before it is used for optimization purposes.